2016
DOI: 10.3168/jds.2015-9868
|View full text |Cite
|
Sign up to set email alerts
|

Predicting colostrum quality from performance in the previous lactation and environmental changes

Abstract: Nine New Hampshire Holstein dairies contributed to a study to investigate if colostrum quality could be predicted by cow performance in the previous lactation and by environmental factors during the 21-d prepartum period. The numbers of days below 5°C (D<), days above 23°C (D>), and days between 5 and 23°C (D) were used in the development of the regression equation. Between 2011 and 2014, 111 colostrum samples were obtained and analyzed for IgG. Producers recorded cow identification number, calf date of birth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
44
5
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 20 publications
13
44
5
9
Order By: Relevance
“…Similar to IgG concentration, colostral protein concentration improved as parity increased, but this was expected, because IgG is a protein (Parrish et al, 1950). Cows that calved in the winter produced 9 g/L more protein than spring-calving cows, but several factors tend to differ across seasons, including diet (Heck et al, 2009;Yasmin et al, 2012), housing, and climate (Nardone et al, 1997;Cabral et al, 2016). Dams immunized against infectious bovine rhinotracheitis before calving produced 11 g/L more protein than nonvaccinated cows.…”
Section: Nutritional Componentsmentioning
confidence: 99%
“…Similar to IgG concentration, colostral protein concentration improved as parity increased, but this was expected, because IgG is a protein (Parrish et al, 1950). Cows that calved in the winter produced 9 g/L more protein than spring-calving cows, but several factors tend to differ across seasons, including diet (Heck et al, 2009;Yasmin et al, 2012), housing, and climate (Nardone et al, 1997;Cabral et al, 2016). Dams immunized against infectious bovine rhinotracheitis before calving produced 11 g/L more protein than nonvaccinated cows.…”
Section: Nutritional Componentsmentioning
confidence: 99%
“…It has been proved that the basic chemical composition and IgG composition of colostrum changes throughout the first six milkings postpartum, and can be influenced by breed or parity . Cabral et al . reported that colostrum yield was negatively correlated with IgG concentration (r = −0.42).…”
Section: Resultsmentioning
confidence: 99%
“…(19) (20) (21). La alimentación inadecuada del recién nacido por la mala calidad nutritiva del calostro, en el primer mes de vida, puede resultar en el crecimiento reducido, mayor riesgo de enfermedad y de muerte (22). En este estudio el promedio de concentración de proteínas en calostro fue 1.69 gr/dl, ligeramente disminuido en comparación a los rangos normales, pero influyente en el crecimiento y desarrollo de los niños del estudio.…”
Section: Tabla N°1: Características De Las Madres Lactantes Y Concenunclassified